SiO2-PbF2-CdF2 glasses and glass ceramics - Silva, MAP; Briois, V; Poulain, M.; Messaddeq, Younes [UNESP]; Ribeiro, SJL (Elsevier B.V., 2003)
Lead-Cadmium fluorosilicate stable glasses were prepared and the vitreous domain region determined in the composition diagram. Characteristic temperatures were obtained from thermal analysis and the structural studies performed illustrate clearly the role played by lead atoms in the glasses crystallization behavior and the glass-forming ability of cadmium atoms. The occurrence of either a cubic lead fluoride or a lead-cadmium fluoride solid solution in crystallizing samples was found to be dependent on Er3+ doping. The optically active ions were found to concentrate in the crystalline phase and in fact play the role of nucleating agent as suggested from X-ray diffraction and EXAFS measurements. (C) 2002 Elsevier B.V. Ltd. All rights reserved.
Keywords: oxifluoride glasses; X-ray absorption spectroscopy; erbium